IMPLEMENTASI PENDIDIKAN KARAKTER DI MASA PANDEMI COVID-19 MELALUI KULIAH KEMUHAMMADIYAHAN BERBASIS PEMBERDAYAAN KELUARGA DHUAFA - M.A., Amirullah; Arifin, Syamsul; Fajri, Muhammad Dwi (Universitas Muhammadiyah Ponorogo, 2021)
The learning process during the COVID-19 pandemic, which is mostly done online, is a challenge for educational institutions in strengthening character values in students, which is an important aspect of educational goals.This research aimed to analyze the implementation of the kemuhammadiyahan subject on empowering poor families during the COVID-19 pandemic in strengthening character values for students. This research was conducted through a qualitative method combining two data collection techniques; review on documents (books and journal articles) and observation of 238 students from 16 departments and 6 faculties who had attended kemuhammadiyahan subject at the University of Muhammadiyah Prof. Dr. Hamka.This research reveals that kemuhammadiyahan subjects using the online learning method combined with field assignments (luring) in the form of empowering poor families have an effect on strengthening student character values. After taking the kemuhammadiyahan subject, students increasingly have a sense and attitude of caring for others (welas asih), sympathy and empathy, social responsibility, gratitude, optimism, generosity, honesty, discipline, patience, citizenship, commitment, compassion, and sincerity. Students also feel that they are increasingly possessing skills such as creative, innovative, communicative and collaborative.This study also shows that kemuhammadiyahan subjects have contributed to helping the poor who were economically affected during the COVID-19 pandemic. Therefore, this kemuhammadiyahan subject model is relevant to the Freedom of Learning-Independence Campus (MBKM)Â policy which was initiated by the Ministry of Education which requires learning which can be implemented based on humanitarian project programs.